Psychosocial Risk Factors and Perceived Stress in University Professors - Tacca Huamán, Daniel Rubén (2019)
University teachers are involved in a work environment where they interact with people (bosses, colleagues, students, etc.) and situations that can cause stress. The main objective of this research was to know the relationship between psychosocial risk factors and the stress perceived by university teachers. The focus of the work was quantitative, the design was correlational and transversal; the sample consisted of 117 university teachers from Lima, Peru. The results indicated that perceived stress is positively related to psychological demands, active work, compensations and double presence of the teachers; however, an inverse relationship was found between stress and social support received. The data showed that teachers who work by contract have a higher level of stress and that the main symptoms experienced are tiredness, not being able to sleep, headaches, poor concentration and variation in appetite. No relevant differences were found in terms of age and sex.